2015
DOI: 10.15406/jpcpy.2015.03.00135
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Literature Relevant to the Experiences of Irish Parents in the Mediation of their Children’s use of Internet Connected Devices

Abstract: This review sets out to explore the relatively new and unique parental experience of mediating children's use of Internet connected devices (ICDs) in Ireland. A coherent understanding of the core concepts that emerged from the literature is presented in a way that connects broad theoretical concepts to specific contexts. An overview of parental experience and the relationship between parental experience and the theoretical aspects of psychology, counselling and psychotherapy is presented. ICDs are briefly expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The narrative of the literature reviewed by Meehan and Hickey [2] however did not infer that parental reaction to child behaviour was a key element of parental mediation strategy. Interestingly, this suggests a connection between the work of Bernstein [24] and Gamble and Gamble [25] in understanding cues or triggers of deception and the wider literature on parental mediation.…”
Section: Theme 1: Parental Mediation (Parental Control and Experiencementioning
confidence: 99%
See 3 more Smart Citations
“…The narrative of the literature reviewed by Meehan and Hickey [2] however did not infer that parental reaction to child behaviour was a key element of parental mediation strategy. Interestingly, this suggests a connection between the work of Bernstein [24] and Gamble and Gamble [25] in understanding cues or triggers of deception and the wider literature on parental mediation.…”
Section: Theme 1: Parental Mediation (Parental Control and Experiencementioning
confidence: 99%
“…The literature reviewed by Meehan and Hickey [2] identified that Nauert [28] and Livingston and Haddon [1] should be acknowledged for how their work helps to create an understanding of parental mediation of online activities. However, the tone of both Nauert's [1] and Livingston and Haddon's [1] work seems to imply that risk should be associated with negative consequences.…”
Section: Theme 3: Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a direct relationship between the parenting styles and trust (Meyers and Gilbert, 2012; Meehan and Hickey, 2015), and in the context of parenting mediations we draw upon the conceptualizations of sociological trust: “[…] of technically competent performance and … of fiduciary obligation and responsibility” (Barber, 1983, p. 165). Here, trust is a process that evolves over time as it is dynamic, context-dependent and conditional (Gubbins and MacCurtain, 2008; Castelfranchi and Falcone, 2010).…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%